Consumers as Financiers: Consumer Surplus, Crowdfunding, and Initial Coin Offerings - Lee, Jeongmin; Parlour, Christine A (Review of Financial Studies, 2022)
Abstract We study the efficiency implications of funding directly provided by consumers. Intermediaries fail to finance all efficient projects, and crowdfunding can improve efficiency. Whereas intermediaries value projects based on cash flows, consumers also receive a consumption benefit. Unique to crowdfunding is the ability of consumers to commit to pay for the benefit, and the degree to which they can do so determines its efficiency. We discuss the implications of introducing a resale market for consumers’ claims, as in the case of initial coin offerings, and the speculation that necessarily accompanies such markets. We provide testable and policy-related implications.